COST EFFECTIVENESS OF PIG FARMING AND WAYS OF HER INCREASE - Сулима, Наталия; Кутовенко, Владимир (SWorldJournal, 2020)
The paper considers the dynamics of the level of production and economic efficiency of pork production at agricultural enterprises, as well as ways to increase them.